IMAGE SMOOTHING MENGGUNAKAN MEAN FILTERING, MEDIAN FILTERING, MODUS FILTERING DAN GAUSSIAN FILTERING - Bambang Yuwono (Telematika, 2010)
Softening image (Image smoothing) aims to suppress the interference (noise) in the image. The disorder usually appears as a result of which is not good penerokan (sensor noise, photographic grain noise) or due to transmission line (the delivery of data) This research has resulted in an application program for image smoothing by four methods: mean filtering, median filtering, Gaussian filtering and filtering modes. Test images used in this study using a sample consisting of twenty 24-bit image and the image of 8 bits. The images are loaded and displayed on the program. Then the image smoothing process was done using the Gaussian method, the mean, median and mode, and displays histogramnya. Parameters measured are the result of image smoothing based on the four methods used, the signal to-noise ratio (SNR), and timing-run.